2021
DOI: 10.1080/09603123.2021.1888894
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from 25 Years of Research into Long term Consequences of Prenatal Exposure to the Dutch famine 1944–45: The Dutch famine Birth Cohort

Abstract: This paper describes the findings of a historical cohort study of men and women born around the time of the Dutch famine 1944-45. It provided the first direct evidence in humans of the lasting consequences of prenatal undernutrition. The effects of undernutrition depended on its timing during gestation, and the organs and tissues undergoing periods of rapid development at that time. Early gestation appeared to be particularly critical, with the effects of undernutrition being most apparent, even without reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 70 publications
(83 reference statements)
0
21
0
2
Order By: Relevance
“…Studies where the long-term consequences of early life exposure to natural disasters or war on brain health have been investigated, however, do provide clues on causality. Individuals who had been prenatally exposed to the 1944–1945 Dutch famine, which struck all social classes, had worse cognitive function, smaller intracranial volume and older appearing brain in late life compared to their contemporaries who had been born just before the famine or had been conceived after it ( De Rooij et al, 2021 ). The quasi experimental nature of this study suggests no confounding by genetics or other variables ( De Rooij et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies where the long-term consequences of early life exposure to natural disasters or war on brain health have been investigated, however, do provide clues on causality. Individuals who had been prenatally exposed to the 1944–1945 Dutch famine, which struck all social classes, had worse cognitive function, smaller intracranial volume and older appearing brain in late life compared to their contemporaries who had been born just before the famine or had been conceived after it ( De Rooij et al, 2021 ). The quasi experimental nature of this study suggests no confounding by genetics or other variables ( De Rooij et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A highly illustrative example of this is a study among individuals who were born around the time of the Dutch famine which showed that those who had been exposed to undernutrition in early gestation tended to be less physically active and showed a preference for a high fat diet at the age of 58 years ( Lussana et al, 2008 ). The group of exposed individuals was also shown to be at higher risk for dyslipidemia, diabetes, and coronary heart disease and to have worse cognitive function at 58 and increased brain age at age 68 ( De Rooij et al, 2021 ). Some studies have demonstrated that both birth weight at the very low end and birth weight at the very high end are associated with lower levels of physical activity in later life ( van Deutekom et al, 2017 ).…”
Section: Early Life Factors and Brain Maintenancementioning
confidence: 99%
“…This is very important, as women are especially vulnerable regarding food insecurity in several life stages, such as pregnancy and frailty. As shown by, e.g., Dutch Hungerwinter studies, it is now well established that malnutrition in utero not only leads to low birth weights or less healthy babies but also impacts the occurrence of non-communicable diseases in later life [ 47 , 161 ]. As such, healthy nutrition during an infant’s first 1000 days, and also including the mothers, is key to healthy populations in all cultures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, alterations in the maternal nutritional environment are now well-recognized as critical factors in shaping the life-long health of the next generation and beyond. One of the most cited observations in humans to date is that of the Dutch Famine (Dutch Hunger Winter) where famine exposure was associated with a range of cardiometabolic outcomes in offspring, effects that were passed to future generations [ 4 ]. To provide empirical evidence to support the emerging epidemiological observations, experimental animal models across a range of species were developed that spanned a range of nutritional challenges across different key developmental windows.…”
mentioning
confidence: 99%